Macromolecular crowder polyethylene glycol delayed the aggregation of chromium-treated bovine serum albumin - Hasan, Samra; Husain, Nazim; Ansari, Neha Kausar; Naeem, Aabgeena (European Journal of Chemistry, 2025)
The structure of proteins is greatly affected by various interacting xenobiotic and lead to the formation of aggregates. Chromium metal, which was initially considered innocent as a nutrient, has been found to induce some abnormalities in the human body recently. Aggregate formation is associated with the occurrence of pathological conditions such as systemic amyloidosis, cystic fibrosis, etc. To have a deeper insight into aggregation susceptibility and structural stability of bovine serum albumin on treating with hexavalent chromium Cr(VI) and the consequences of macromolecular crowding on the native conformation of the protein, the chromium concentration ranged from 0-100 µM where K2Cr2O7 was used as the Cr (VI) source. Disruption of native bovine serum albumin (BSA) assembly and formation of aggregates at 50 µM Cr(VI) was unveiled by increased turbidity and fluorescence at 350 nm, reduced intrinsic fluorescence with 10 nm and 20 nm blue shifted enhanced ANS spectra respectively. Significantly enhanced, the ThT fluorescence alone side sigmoidal curve with no lag phase and a 10 nm red shift in congo red spectra sustained conformational changes and indicated aggregation of BSA upon incubation with Cr(VI). Circular dichroism (CD) results showed the disappearance of negative minima at 208 and 222 nm, which confirms the transition of native helical structure to non-native beta sheets. Furthermore, the comet assay showed that Cr-treated BSA aggregates were found to be genotoxic, as an increase in tail length of 11.3 μm had been observed. Crowded microenvironment was mimicked by PEG-4000; a polyethylene glycol, was witnessed to prominently preserve conformational stability of BSA upon treatment with Cr(VI) as all results observed were close to that of native. The decrease in turbidity, fluorescence at 350 nm accompanied by a reduction in 8-anilinonaphthalene-1-sulfonic acid (ANS) and thioflavin T (ThT) fluorescence further verified the inhibition of aggregate formation in the presence of PEG-4000. Furthermore, the increased intrinsic fluorescence, decreased congo red absorption and reduced tail length of 3.4 μm in the comet assay were in co-relation with the above data. The macromolecular crowder PEG-4000 was efficient in delaying the aggregation of Cr-treated BSA, as the kinetics showed a sigmoidal curve with the lag phase. Based on these findings, it could be hypothesized that the native structure was maximally retained in the presence of 100 mg/mL of PEG-4000, demonstrating braking of aggregate formation. It can be established that explicit consideration of macromolecular crowding using a relevant range of inert crowding agents must be a prerequisite for studies concerning intracellular conformational behavior of proteins and enhanced their stability under stress conditions and devising protein formulations with enhanced conformational stability.